Soluble fms-like tyrosine kinase-1-to-placental growth factor ratio and time to delivery in women with suspected preeclampsia - Zeisler, H; Llurba, E; Chantraine, F; Vatish, M; Staff, A; Sennström, M; Olovsson, M; Brennecke, S; Stepan, H; Allegranza, D; Dinkel, C; Schoedl, M; et al. (Lippincott, Williams & Wilkins, 2016)
To assess the association of a serum soluble fms-like tyrosine kinase 1-to-placental growth factor (sFlt-1-to-PlGF) ratio of greater than 38 with time to delivery and preterm birth.Secondary analysis of an observational cohort study that included women 18 years of age or older from 24 to 36 6/7 weeks of gestation at their first study visit with suspected (not confirmed) preeclampsia. Participants were recruited from December 2010 to January 2014 at 30 sites in 14 countries. A total of 1,041 women were included in time-to-delivery analysis and 848 in preterm birth analysis.Women with an sFlt-1-to-PlGF ratio greater than 38 (n=250) had a 2.9-fold greater likelihood of imminent delivery (ie, delivery on the day of the test) (Cox regression hazard ratio 2.9; P<.001) and shorter remaining time to delivery (median 17 [interquartile range 10-26] compared with 51 [interquartile range 30-75] days, respectively; Weibull regression factor 0.62; P<.001) than women with an sFlt-1-to-PlGF ratio of 38 or less, whether or not they developed preeclampsia. For women who did not (n=842) and did develop preeclampsia (n=199), significant correlations were seen between an sFlt-1-to-PlGF ratio greater than 38 and preterm birth (r=0.44 and r=0.46; both P<.001). Among women who did not develop preeclampsia, those who underwent iatrogenic preterm delivery had higher median sFlt-1-to-PlGF ratios at their first visit (35.3, interquartile range 6.8-104.0) than those who did not (8.4, interquartile range 3.4-30.6) or who delivered at term (4.3, interquartile range 2.4-10.9).In women undergoing evaluation for suspected preeclampsia, a serum sFlt-1-to-PlGF ratio greater than 38 is associated with a shorter remaining pregnancy duration and a higher risk of preterm delivery.